Framing the Digital Discourse on Childfree in BincangSyariah.com: A Maqāṣid al-Sharīʿah Perspective - Umumah, Mega Zakhirul; Rizki Dwi Aprilianto; Achmad Afandy; Muhammad Iqbal Wi'an Ekaputra; Nur Lailatul Musafa'ah; Shavia, Andina Najma (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2025)
The discourse on childfree has emerged as a complex and multidimensional topic within both digital spaces and contemporary Islamic legal thought. When articulated online, this discourse reflects varying forms of partiality and narrative framing, shaped by the distinctive character and ideological orientation of each platform. This study aims to explore how BincangSyariah.com presents the issue of childfree through the lens of maqāṣid al-sharīʿa. Employing a normative-legal methodology with a conceptual and philosophical approach, the research utilizes qualitative-descriptive analysis. The primary data consists of selected articles on childfree published by BincangSyariah.com, while secondary sources include classical and contemporary Islamic legal literature, alongside scholarly discussions on gender and digital media. Analytical tools include Robert N. Entman’s framing theory and maqāṣid al-sharīʿah. The findings reveal that BincangSyariah.com presents childfree not as a deviation from Islamic norms, but as a legitimate life choice when supported by rational considerations and contextualized within Islamic legal and ethical discourses. The site provides a discursive space where the perspectives of Islamic law, hadith, gender, and social analysis intersect. From a maqāṣid al-sharīʿa perspective, the framing aligns with the objectives of preserving intellect (ḥifdh al-ʿaql) and lineage (ḥifd al-nasl). This study highlights the pivotal role of Islamic digital media in addressing contemporary socio-religious issues while upholding ethical commitments rooted in Islamic law.